Credit Risk-Return Puzzle: Asian Countries Representative - Singagerda, Faurani Santi; Suryanto, Tulus; Sudjana, Jesscia Christina (Universitas Negeri Malang, 2017)
This Â research Â investigates Â the Â presence Â ofÂ Credit Â Risk-Return Â Puzzle Â on Â Indonesia, Â China, Japan and Singapore, Â by analyzing Â the relationship Â betweenÂ credit risk and stock return with the utilization of credit ratings from Moodyâs to represent credit risk. The data comprises of monthly data from January 2001 to December 2015, compiled in an unbalanced panel and then regressed with the Hausman-Taylor Â EstimatorÂ due to the presence Â of time-invariant Â variablesÂ such as countries Â and country classifications within the dataset.The results from this research show that Credit Risk-Return Puzzle exists in both developed andÂ developing Â market for long-term Â credit ratings, proven by the negativeÂ relationship Â betweenÂ stock return and credit ratings. On the other hand Credit Risk-Return Puzzle does not exist in the case of credit rating changes in terms of direction but do show some signs of existence through difference in magnitude, Â asÂ different Â reasons Â underlying Â credit Â rating Â changes Â such Â asÂ leverage Â changes Â can change the direction of stock price movement.Â Keywords: credit risk-return puzzle, credit rating announcements, credit risk, impact of rating changes, decoupling-recoupling hypothesis